2021
DOI: 10.1016/j.chest.2020.10.083
|View full text |Cite
|
Sign up to set email alerts
|

Lower Respiratory Tract Myeloid Cells Harbor SARS-Cov-2 and Display an Inflammatory Phenotype

Abstract: Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) pneumonia may induce an aberrant immune response with brisk recruitment of myeloid cells into the airspaces. 1 Although the clinical implications are unclear, others have suggested that infiltrating myeloid cells may contribute to morbidity and mortality rates during SARS-CoV-2 infection. [1][2][3] However, few reports have characterized myeloid cells from the lower respiratory tract, which appears to be the primary site of viral-induced disease, du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Studies of Middle East Respiratory Syndrome (MERS) Coronavirus have demonstrated infection of monocyte-derived macrophages with subsequent secretion of inflammatory cytokines such as CXCL10 and CXCL8 (IL-8)39 . Conversely, SARS-COV abortively infects human macrophages, but triggers production of CXCL10 and CCL240,41 .Consistent with our findings of activated monocytes with induced expression of viral sensing and IFN response genes, an earlier study has shown that lower respiratory tract myeloid cells can harbor SARS-COV-2 and display an inflammatory phenotype42 .Furthermore, recent work demonstrated that infected monocytes in bronchoalveolar lavage samples from patients with COVID-19 participate in a positive feedback loop in which infected myeloid cells produce T cell chemoattractants, recruiting T cells into the lung43 . These T cells then secrete IFN-γ, contributing to release of inflammatory cytokines from alveolar macrophages, thereby promoting further T cell activation43 .…”
supporting
confidence: 91%
“…Studies of Middle East Respiratory Syndrome (MERS) Coronavirus have demonstrated infection of monocyte-derived macrophages with subsequent secretion of inflammatory cytokines such as CXCL10 and CXCL8 (IL-8)39 . Conversely, SARS-COV abortively infects human macrophages, but triggers production of CXCL10 and CCL240,41 .Consistent with our findings of activated monocytes with induced expression of viral sensing and IFN response genes, an earlier study has shown that lower respiratory tract myeloid cells can harbor SARS-COV-2 and display an inflammatory phenotype42 .Furthermore, recent work demonstrated that infected monocytes in bronchoalveolar lavage samples from patients with COVID-19 participate in a positive feedback loop in which infected myeloid cells produce T cell chemoattractants, recruiting T cells into the lung43 . These T cells then secrete IFN-γ, contributing to release of inflammatory cytokines from alveolar macrophages, thereby promoting further T cell activation43 .…”
supporting
confidence: 91%
“…These findings are relevant as MP-TF positively correlates with leukocytes, D-dimer, inflammatory parameters, and is associated with an increased thrombotic risk, disease severity and mortality in SARS-CoV-2 [67,68]. With respect to cellular sources for TF, there is evidence for participation of neutrophils [21], platelet-monocyte aggregates and [28] macrophages [69] although transcripts for TF were not upregulated in monocytes in SARS-CoV-2 [38], in contrast with sepsis [17,51,70]. At last, our univariate analysis supports the view that coagulation dysregulation in COVID-19 infection has a multifactorial etiology.…”
Section: Discussionmentioning
confidence: 87%
“…Earlier studies have highlighted the paramount role of myeloid antigen-presenting cells (APCs), such as macrophages and dendritic cells (DCs), in mediating an antiviral inflammatory response, which is exacerbated in severe COVID-19 cases (Bain et al, 2021;Merad and Martin, 2020). A critical role of lung macrophages in inducing the inflammation associated with the pathologic sequelae of SARS-CoV-2 infection has been confirmed also in nonhuman primates (NHP) (Hoang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%